UPBRINGING AS A MEANS OF THE LIFE CREATION IN ITS BEST POINTS - Leonid I. Luriye (Obrazovanie i Nauka, 2015)
The research is aimed at emphasizing the updating necessity of pastoral work in Russian schools and universities due to changed economic, social and ideological conditions of development of a society. Methods. The research involves the method of socially-pedagogical analysis of current issues in the Russian upbringing and educational system. Results. The author gives own representation of upbringing process, as contextual, complex, system-directed and sociocultural effect on a human being that is conformed to the person, society and state development. It has been affirmed that upbringing process is to outgrow in self-education and strategy development of the realised self-restrictions caused by conventional values and morality norms. The author considers the reasons of the current crisis of educational activity; the solution ways are proposed. Scientific novelty. The research findings give a detailed analysis of modern educational system status that is caused by the “pressure” of modern pedagogics; the author finds out and enumerated the reasons of weak sociocultural of pedagogic society leadership and initiativity. The author proposes the new conception of upbringing activity based on liberally-democratic vision of society structure that provides an opportunity to define the process of world perception formation and active stance towards life of a "cultivated" person. Practical significance. Implementation of the research recommendations can be useful for efficient upbringing activity management that is to unite all the members of educational process.